2022
DOI: 10.1155/2022/3997190
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Activity of Quercetin: An Updated Review

Abstract: Quercetin, a natural flavonoid compound with a widespread occurrence throughout the plant kingdom, exhibits a variety of pharmacological activities. Because of the wide spectrum of health-promoting effects, quercetin has attracted much attention of dietitians and medicinal chemists. An updated review of the literature on quercetin was performed using PubMed, Embase, and Science Direct databases. This article presents an overview of recent developments in pharmacological activities of quercetin including anti-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 96 publications
(119 reference statements)
0
11
0
Order By: Relevance
“…These effects are achieved through their actions on multiple signaling pathways and targets, as indicated by previous studies. [117][118][119] Modern pharmacological studies have indicated that prolonged administration of natural products yields superior results in alleviating depressive-like behaviors in rats compared to single-dose administration. [76] It worth noting that many natural products exhibit potent antidepressant effects at higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are achieved through their actions on multiple signaling pathways and targets, as indicated by previous studies. [117][118][119] Modern pharmacological studies have indicated that prolonged administration of natural products yields superior results in alleviating depressive-like behaviors in rats compared to single-dose administration. [76] It worth noting that many natural products exhibit potent antidepressant effects at higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor aspect involves breast cancer, liver cancer, colon cancer, etc. [ 65 , 66 , 67 , 68 , 69 , 70 ]. However, there are application limitations related to the stability of use in vivo, which limits the use of quercetin [ 71 ].…”
Section: Polyphenolic Compoundsmentioning
confidence: 99%
“…It is a plant secondary metabolite with antioxidant activity (Zhi et al, 2023). In the past decades, quercetin has been widely used in clinical practice for various diseases due to its superior activity, including cancer, arthritis, neurodegenerative diseases and cardiovascular diseases (Wang et al, 2022). There are numerous studies on quercetin in the treatment of AS.…”
Section: Ros Promotes Ox-ldl Production and Aggravates Endothelial Dy...mentioning
confidence: 99%